Phần mềm thẩm định dự toán và quyết toán công trình xây dựng cơ bản - Ngọc, Trần Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper we propose a package of programs (PP) written in FoxPro for evaluating estimated cost and the final balance sheet of a construction work. This PP has been used in the Bank for investment and development of Hanoi and was proved to be a stable and useful software.